Metaphorische Kollokationen – zum Problem ihrer theoretischen Festlegung und empirischen Erforschung - Keglević Blažević, Ana (Slavia Centralis, 2022)
The present paper gives a theoretical overview of the subcategory of metaphorical collocations and their different research approaches. Collocations have been examined from different perspectives. Despite that fact, there has still not been a unanimously accepted definition of the term coined. Regardless of the different approaches, it can be observed that some collocations show a kind of change in meaning. These are referred to as metaphorical collocations and are understood as a subcategory. The collocate of the metaphoricalcollocation has more than one meaning, and is, therefore, polysemous. Metaphorical collocations are taken into account in different typologies and classifications, but, so far, there have only been a few studies that deal with this subcategory. These collocations thus represent a phenomenon that has not yet been researched adequately.
Keywords: collocations; metaphorical collocations; conceptual metaphor; collocate; German; Croatian